2016
DOI: 10.1038/srep31739
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Local Structure Disorder and the Relaxor State in (Bi1/2Na1/2)TiO3-BaTiO3

Abstract: Lead-based relaxor ferroelectrics are key functional materials indispensable for the production of multilayer ceramic capacitors and piezoelectric transducers. Currently there are strong efforts to develop novel environmentally benign lead-free relaxor materials. The structural origins of the relaxor state and the role of composition modifications in these lead-free materials are still not well understood. In the present contribution, the solid-solution (100-x)(Bi1/2Na1/2)TiO3-xBaTiO3 (BNT-xBT), a prototypic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 52 publications
(91 reference statements)
3
34
1
1
Order By: Relevance
“…This indicates that, without any prepoling, NBT- x BT shows typical relaxor behaviors in the BT composition of 5~8% near the MPB. This result is consistent with a recent dielectric study, which determined that relaxor state is maintained over a specific composition range near the MPB [16]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that, without any prepoling, NBT- x BT shows typical relaxor behaviors in the BT composition of 5~8% near the MPB. This result is consistent with a recent dielectric study, which determined that relaxor state is maintained over a specific composition range near the MPB [16]. …”
Section: Resultssupporting
confidence: 93%
“…The broad minimum of ν B and the concomitant broad maximum of Γ B without any sharp, discontinuous changes indicate that there is no long-range ferroelectric order at low temperatures. This is consistent with the recent 23 Na NMR results, which showed that NBT- x BTs near the MPB exhibit substantial octahedral tilting disorder and relaxor states [16]. The microscopic origin of the gradual mode softening of the LA mode is attributed to the coupling between the strains caused by acoustic waves and local polarizations of the dynamic PNRs [34].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] They found a sequence of phase transitions from the low temperature rhombohedral via a tetragonal to a high temperature cubic phase. These findings were confirmed by X-ray diffraction studies, 7,12,13,[18][19][20][21][22][23][24][25] other characterization techniques 13,18,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and theoretical ab initio studies. [41][42][43][44][45][46][47][48] However, some of the transmission electron microscopy (TEM) studies reported an intermediate orthorhombic phase.…”
Section: Introductionmentioning
confidence: 68%
“…The difficulty in assigning a definitive average structure for NBT-based materials and the mismatch with the macroscopic properties stems from the short range order/disorder present in these types of materials. Several studies have tried to tackle this problem using EXAFS 23,24 , NMR 25 , X-ray diffuse scattering 2631 , TEM 3235 , pair-distribution function (PDF) 5,36 or DFT calculations 3741 . EXAFS measurements 23 suggest a highly distorted local coordination for Bi with a shorter minimum Bi-O bond of 2.2 Å than the one proposed by diffraction experiments, which is 2.5 Å. RMC refinement of PDF data reveals an anisotropic Bi-O bonding 5,36 which suggest that Bi is strongly displaced off-center in the oxygen polyhedron.…”
Section: Introductionmentioning
confidence: 99%